A case of hereditary metachronous bilateral triple-negative breast cancer that was highly sensitive to carboplatin. Issue 4 (14th April 2021) - Wu, Rongrong; Adachi, Kayo; Koyama, Yoichi; Orimoto, Kyoko; Okazaki, Miki; Asaoka, Mariko; Teraoka, Saeko; Ueda, Ai; Miyahara, Kana; Kawate, Takahiko; Kaise, Hiroshi; Yamada, Kimito; et al.
Abstract: A 52-year-old woman with a strong family history of breast cancer was diagnosed as having triple-negative breast cancer (TNBC) in her right breast. Neoadjuvant chemotherapy (NAC; four cycles of epirubicin/cyclophosphamide/5-fluorouracil) was performed, followed by breast-conserving surgery and axillary lymph node dissection. Histopathological analysis of the surgical specimens demonstrated a few focal tumor cells remaining in the stroma, but not a pathological complete response (pCR). Weekly paclitaxel was subsequently added to the treatment regimen. A total of 17 months after the adjuvant treatments, TNBC recurred in her left breast with massive lymph node metastasis. Because of the early recurrence after standard treatment, NAC was administered together with carboplatin and paclitaxel. Histopathological analysis of the partially resected breast and axillary lymph nodes demonstrated a pCR. No recurrent disease was found 2 years after the second TNBC treatment. This case underlines the importance of platinum-based chemotherapy and prophylactic mastectomy for patients with BRCA dysfunction.